Restricted Maximum Likelihood Method As An Alternative Parameter Estimation in Heteroscedastic Regression - Masrokhah, Dwi; Soehono, Loekito Adi; Astutik, Suci (CAUCHY, 2018)
Students are part of the community who have an income. The income of students are pocket money, scholarships, part-time jobs and so forth. They are trying to become trendsetter in get dress and . The consumption patterns are very influential in behavior of saving. If the savings increases not only the public funds will increase but also the investment. If the investment increases the economic growth has also increased. The purpose of this research is to estimate multiple regression parameters using REML methods in modeling the student’s saving in Faculty of Mathematics and Natural Science, Brawijaya University. The variables used were X_1= The student’s age (years), X_2= The amount of income of student’s parent (thousand rupiah), X_3= The amount of student’s pocket money (thousand rupiah), X_4= The amount of student’s additional income (thousand rupiah), X_5= The amount of student’s consumption (thousand rupiah) and Y= The amount of student’s saving (thousand rupiah).REML method can overcome heteroscedasticity error variance and unbiased estimator. The model of student’s saving is using REML method as follows:Y ̂_i= -1855,66 +121,5 X_1+0.0098X_2+0.0524 X_3+0.5587 X_4-0.5851X_5Student’s saving affected by: student’s age (years), the amount of student’s additional income (thousand rupiah), and the amount of student’s consumption (thousand rupiah).